Analisis Stabilitas Perbankan Syariah dan Konvensional di Negara-Negara Kawasan MENA - Anggraini, Fitri; Taufik, Taufik; Muizzuddin, Muizzuddin; Andriana, Isni (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the stability of Islamic and conventional banking in 18 countries in the Middle East and North Africa (MENA) region and the factors that influence it. This study uses panel data regression by taking a sample of 86 Islamic banks and 174 conventional banks during the 2011-2019 period. The analytical tools used are z-score analysis and panel data regression. The regression results show that simultaneously CAR, FDR, BOPO, NPF have a significant effect on the stability of Islamic banks. Partially, CAR and FDR have a significant positive effect, while BOPO has a significant negative effect. Then NPF has no influence on the stability of Islamic banks. Meanwhile for conventional banks CAR, LDR, BOPO, NPL simultaneously have a significant effect on the stability of conventional banks. Partially CAR and LDR have a significant positive effect, BOPO has a significant negative effect while NPL has no effect on the stability of conventional banks.